Antimicrobial and antibiofilm effects of crude and microencapsulated guava leaf extracts against Enterococcus faecalis and Staphylococcus epidermidis - Gutierrez-Montiel, Daniela; Guerrero-Barrera, Alma L.; Moreno-Flores, Adriana C.; Ramírez-Castillo, Flor Y.; Chávez-Vela, Norma A.; Martínez-Ávila, Guillermo Cristian Guadalupe; Rico-Martínez, Roberto; Costa, Matheus de O.; Galindo-Guerrero, Fabiola; Avelar-Gonzalez, Francisco J.; Ornelas-Garcia, Ingrid G.; Franco-Ramírez, Omar (Frontiers in Antibiotics, 2025)
BackgroundStaphylococcus epidermidis and Enterococcus faecalis are nosocomial microorganisms that have gained attention in recent times due to the increasing reports of antimicrobial-resistant strains, which are leading to infections that are progressively harder to eradicate. One of the most important resistance mechanisms employed by these two bacteria is biofilm formation, which provide them with physical and chemical protection from antimicrobial agents.MethodsThis study assessed the antimicrobial activity of crude and microencapsulated extracts of Psidium guajava L., an agro-industrial waste product widely available in guava-producing countries, using the microdilution technique. Additionally, anti-adhesion activity was analyzed in microplates and by confocal laser scanning microscopy (CLSM).ResultsGuava leaf extract reduced the growth of all three bacterial strains evaluated. For Staphylococcus epidermidis (ATCC 12228), the minimum inhibitory concentrations (MICs) were 25 mg/ml for the crude extract and 0.625 mg/ml for the microencapsulated form. In contrast, for Enterococcus faecalis (ATCC 29212 and a vaginal clinical isolate), MIC values were greater than 50 mg/ml and 5 mg/ml, respectively. Furthermore, both extracts exhibited anti-biofilm activity by reducing bacterial adhesion.Conclusionmicroencapsulation allowed a reduction in the extract concentration and guava leaf extract shows potential as an antimicrobial agent for future application.